DINAMIC INTERN CONFLICT CIVIL SOCIETY ORGANIZATION STUDY CHASES : PEMUDA PANCASILA PEKANBARU ORGANIZATION 2013 - Kurniawan, Yudhi; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The study curry out to analyze the dinamic conflict that happened on organize civil society. Pemuda Pancasila city of Pekanbaru which happen in 2013. The Pemuda Pancasila organization biggest itself is the biggest civil organization in Indonesia, which have a million member that spread throught all of the indonesian province, so it can be said the Pemuda Pancasila is the strongest and care organization for indonesia people.This study is qualitative study, the data collection techniques is descriptive analysis. This research uses documentation (observation) and interviews with key informants as an information object that aims to achieve the goal to get the information in this study. The type of data used in this study are primary and secondary data obtained from direct observation and interviews with key informants in this study.Pemuda Pancasila city of Pekanbaru is the known biggest civil organization by the number of membership. At this rate specudate an add that can be cause a trouble that require leader of Pemuda Pancasila Indonesia itself to solve this problem. The problem mainly around the leadership, where the member of Pemuda Pancasila to take a leadership by muscablub.Muscablub comes from member of Pemuda Pancasila that feel there is injustice in the organization. Also because of lock of transparancy at majelis pimpinan cabang (MPC) Pekanbaru. Wich stimulate muscablub to happen. Pemuda Pancasila is an Organization that got a funding from government (APBD), which make some member quistioning it, and then want to muscablub because of the lack of information and transparancy at the allocation of APBD.Key note: civil society organization, conflict, pemuda pancasila.